Mapping The Covid-19 Global Response: From Grassroots To Governments - Akligoh, Harry; Havemann, Jo; Restrepo, Martin; Obanda, Johanssen (My University, 2020)
Visual map at kumu.io/access2perspectives/covid19-resources Data set doi: 10.5281/zenodo.3732377 // available in different formats (pdf, xls, ods, csv,) Correspondence: (JH) info@access2perspectives.com
Keywords: Africa; COVID-19; data visualization